2015
DOI: 10.1177/0883073815585352
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Fusion for Scoliosis in Rett Syndrome With an Emphasis on Respiratory Failure and Opioid Usage

Abstract: Our objective was to characterize our experience with 8 patients with Rett syndrome undergoing scoliosis surgery in regard to rates of respiratory failure and rates of ventilator-acquired pneumonia in comparison to patients with neurologic scoliosis and adolescent idiopathic scoliosis. This study was a retrospective chart review of patients undergoing scoliosis surgery at a tertiary children's hospital. Patients were divided into 3 groups: (1) adolescent idiopathic scoliosis, (2) neurologic scoliosis, and (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…In fact, a study comparing patients with RTT and cerebral palsy showed that the incidence of respiratory failure and prolonged use of positive pressure ventilation were significantly more common in RTT girls after posterior spinal fusion [96]. Similar results were obtained in a previous report investigating the same parameters following surgical treatment for scoliosis in RTT girls and patients affected by adolescent idiopathic scoliosis and neurologic scoliosis [97]. RTT patients undergoing spine surgery were also evaluated in another study aimed at identifying the perioperative adverse events associated with the surgical procedure [98].…”
Section: Interactions Of Bone With Other Organ Systems In Rttsupporting
confidence: 80%
“…In fact, a study comparing patients with RTT and cerebral palsy showed that the incidence of respiratory failure and prolonged use of positive pressure ventilation were significantly more common in RTT girls after posterior spinal fusion [96]. Similar results were obtained in a previous report investigating the same parameters following surgical treatment for scoliosis in RTT girls and patients affected by adolescent idiopathic scoliosis and neurologic scoliosis [97]. RTT patients undergoing spine surgery were also evaluated in another study aimed at identifying the perioperative adverse events associated with the surgical procedure [98].…”
Section: Interactions Of Bone With Other Organ Systems In Rttsupporting
confidence: 80%
“…The literature does not contain any studies which evaluate the corrections possible in Rett syndrome. This may be because of its rarity, or the technical challenges which have historically been present in managing these patients, the perioperative morbidity, and difficulty in monitoring their neurological status during the procedures [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…There were 133 patients with adolescent idiopathic scoliosis, 48 patients with neurologic scoliosis, and 8 patients with Rett syndrome. They found that patients with Rett syndrome undergoing scoliosis surgery have higher rates of respiratory failure and longer ventilation times in the postoperative period when compared with both adolescent idiopathic scoliosis and neurologic scoliosis patients [ 12 ].…”
Section: Discussionmentioning
confidence: 99%